Design of Installation Photography Work: Menembus Rikuh Memikat Kerinduan - Vega Giri Rohadiat (Universitas Pasundan, 2025)
Menembus Rikuh Memikat Kerinduan is a manifestation of personal reflection in seeing and experiencing various kinds of relationships that occur in a family. Over time, there have been many changes in the intimate relationship between parents and children caused by several factors such as increasing age followed by physical changes, social life outside the home which has an impact on the emergence of distance and limitations of emotional interaction between family members. Based on this phenomenon, the author aims to create a work of installation photography by combining several media in making the work including performance, photography and video in the process of making the work. This research method uses a qualitative method to examine the deeper meaning of the phenomenon that the author found. The process of creating the work was carried out as an effort by the author to break through the awkward feelings towards both parents that have been felt and become a cathartic activity in the process of realizing the work, namely an activity carried out as one way to improve the author's relationship with parents and return to being a family full of emotional ties without distance and alienation.